Principal Leadership and Teacher Discipline : Their Impact on Education Quality in Gandus District State Elementary Schools - Vera Cecilia; Nur Ahyani; Suherman Suherman; Edi Harapan (FKIP, Universitas Palangka Raya, 2025)
This study aims to determine and analyze the Influence of Principal Leadership and Teacher Discipline on the Quality of Education in SD Negeri Se Gandus District, Palembang. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study is 169 teachers of State Elementary School in Gandus District, Palembang, which is a number. Data collection techniques use questionnaires. The data analysis technique uses quantitative descriptive analysis techniques and multiple regression. The results of this study stated that 1) there was a significant influence of the principal's leadership on the quality of education in Gandus Palembang District; 2) there was a significant influence of teacher discipline on the quality of education in Gandus Palembang District; 3) there is a significant influence on the leadership of the principal and the discipline of teachers on the quality of education in Gandus District, Palembang.